Behaviour of biomass multicomponent ashes as adsorbents - Deokar, Sunil K.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Current Science, 2016)
Physico-chemical characteristics of rice husk ash and baggase fly ash, commonly referred to as biomass ashes enable their use as adsorbents. Contrary to normal expectations, it is observed that larger particles have more number, narrower and deeper pores than smaller particles. As a consequence they have higher pore volume, total surface area and hence adsorption capacity. Also, the uptake rate of adsorption depends on the silica to carbon ratio, which is seen to be smaller for larger particles and hence they take a longer time to reach equilibrium. The extent of carbon content determines the capacity, whereas silica to carbon ratio determines the kinetics of adsorption. Removal of 2,4-dichlorophenoxyacetic acid, from aqueous solution was chosen as a representative case for study and the results obtained are compared with earlier reported results.
Keywords: Adsorption capacity; bagasse; biomass ash; rice husk; silica to carbon ratio

Effect of rice husk particle size on ZSM-5 physico-chemical properties for selective formation of 1,3,5-trimethyl-2-benzylbenzene (Pharmaceutical Intermediate) - Ghuge, Gorakh; Niphadkar, Prashant; Rathod, Simmy; Bokade, Vijay V. (ChemistrySelect, 2021)
Rice husk, rich in silica and abundantly available as waste, is presently destroyed by burning, which creates environmental issues. Thus, it will be advantageous if this rice husk waste can be used for preparation of valuable products. One of the application is its use as silica source in the synthesis of zeolites like ZSM-5, which are silico-aluminates. Rice husk waste is available in wide range of particle sizes in agricultural farms. There is no study available in open literature on use of these wide particle ranges for its direct application. This paper is an attempt to use wide particle size rice husk, its effect on ZSM-5 synthesis and its physico-chemical properties. Further these prepared ZSM-5 catalyst was evaluated for benzylation of mesitylene reaction. The study found that, rice husk of 600 mu m particle size is optimum as far as ZSM-5 synthesis, its physicochemical properties and further its application in mesitylene benzylation reaction.
Keywords: Mesitylene; Particle size; rice husk; Silica Source; ZSM-5

Nanosilica from Averrhoa bilimbi juice pre-treated rice husk: preparation and characterization - Dominic, C. D. Midhun; Neenu, K. V.; Begum, P. M. Sabura; Joseph, Rani; Rosa, Derval dos Santos; Duan, Yongxin; Balan, Aiswarya; Ajithkumar, T. G.; Soumya, Mary; Shelke, Ankita; Parameswaranpillai, Jyotishkumar; Badawi, Michael (Journal of Cleaner Production, 2023)
The preparation of nanosilica from rice husk without using any concentrated mineral acids is a novel concept. This work proposes a bioleaching strategy to remove metallic impurities from rice husk for the preparation of nanosilica. Herein, nanosilica (BJRHS) was prepared by calcinating Averrhoa bilimbi juice pre-treated rice husks in a muffle furnace. The chemical and atomic structures of commercial precipitated silica (CS), rice husk ash (RHA), and BJRHS were analyzed using different analytical techniques. The optimal leaching time, calcination temperature, and calcination time were 1 h, 500 degrees C, and 6 h respectively. The particle size of BJRHS was found to be 6-12 nm, which is less than that of RHA and CS. The BET surface area of BJRHS (204 m2/g) was found to be greater than RHA (110.5 m2/g) and CS (172.1 m2/g). Mesoporous nanosilica with excellent surface area and purity was produced sustainably from rice husk which could be recommended to use in the field of catalysis, polymer technology, etc.
Keywords: Averrhoa bilimbi juice; Bioleaching; Nanosilica; rice husk